Strengthening BPKN Governance in Realising a Synergistic and Sustainable Consumer Protection Ecosystem - Joko Nugroho; Antoni Ludfi Arifin (Greenation International Journal of Law and Social Sciences, 2026)
This study is motivated by the increasing complexity of consumer protection in the context of economic globalisation and digital transformation, which has introduced new risks and exposed weaknesses in institutional governance. Previous studies on consumer protection governance have primarily focused on regulatory and policy aspects, with limited attention to institutional integration and governance mechanisms. Moreover, the concept of a consumer protection ecosystem remains underdeveloped, particularly in explaining how multi-actor collaboration and adaptive governance can be operationalised. This study aims to analyse the strengthening of governance within the National Consumer Protection Agency (BPKN) as a strategic actor in developing a synergistic and sustainable consumer protection ecosystem. This research employs a qualitative approach using a systematic literature review of academic journals, books, and policy documents published between 2015 and 2025. Data were analysed using thematic analysis focusing on institutional governance, coordination mechanisms, and digital transformation challenges. The findings indicate that the main challenges lie in fragmented institutional arrangements, weak inter-agency coordination, limited data integration, and low consumer literacy. This study proposes that BPKN should function as a central node within a governance-based consumer protection ecosystem by strengthening coordination, data-driven policy systems, and institutional capacity. The study contributes by offering a conceptual model of consumer protection as an integrated governance ecosystem, emphasising collaboration, adaptability, and evidence-based policymaking.